PERANCANGAN APLIKASI PERHITUNGAN KUAT NOMINAL KOLOM BETON BERTULANG BERBASIS APLIKASI ANDROID - Ivana Madeline Diamanta; Richard Frans; Hendry Tanoto Kalangi (LPPM Universitas Abdurrab, 2024)
Nowadays, the use of applications which is to analyze or to design in civil engineering are necessary. Besides being able to solve the analysis and design problem, the use of applications is an effective for computational time problems compared to manual calculations. Column is one of the most crucial elements in a building construction where the role of the column is to support and distribute the loads on the building structure. In general, in designing a column, column interaction diagram with a certain cross section is made and compare the capacity of the column sections (Pn and Mn) from the column interaction diagram with the required strength values (Pu and Mu). Android is an operating system on smartphones and is popular nowadays. The aim of this research is to develop an Android-based application using Android Studio with Java programming language to create a column interaction diagram of several types of columns, i.e. square column with 4 (four) side reinforcement, square column with reinforcement on 2 (two) sides, and circular columns. The results obtained from the developed application are compared with manual calculations (reference). The difference of result obtained is less than 1% which means that there is no significant comparison between the designed application and manual calculations (reference). Therefore, the developed application can be practically used as an alternative in designing columns.